Smanggi Berbatik Collaborative Workshop in Scientific Writing Training Activities for Students of SMAN 1 Sragi - Sumargono Sumargono; Rinaldo Adi Pratama; Yusuf Perdana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The knowledge of both teachers and students regarding the writing of scientific papers, whether related to natural phenomena, history, or local wisdom in Lampung, is still very lacking. This could be due to the fact that the majority of educators and students are still focused on formal learning activities, while improving scientific writing skills has not yet become a priority for students at SMA N 1 Sragi in the Sragi District. The main objective of this service is to educate high school students thru the collaboration of Kombel